Time Management (Global Journal of Management and Business Research, 2013)
Scores of articles and books have been written on managing time more effectively and using time more wisely. They all are, presumably, well intentioned, and all have something to say to the executive who really wants to "get a better handle on how I use my time." But, as Peter Drucker observes, "Most discussions of the executive's task start with the advice to plan one's work. This sounds eminently plausible. The only thing wrong with it is that it rarely works. The plans always remain on paper, always remain good intentions. They seldom turn into achievement." Perhaps the reason that Drucker's observation is correct is that most of us pay lip service to the concept of selfdiscipline. We recognize it is "right" and "good." But we are not really convinced that we want to turn ourselves into automations in the work situation and become the most efficient, hardest working, hard-driving executive in the cemetery. We unconsciously feel that working hard and efficiently is working at "a killing pace," and we don't want to do that at the expense of our life force. When we say "I'm just killing time," what we really mean is "time is killing me -and I'm not ready to go." That is why efficiency planning seldom works -efficiency is the wrong first objective.
Keywords: performance; discipline; selection; efficient; priority